Comparison of utility of tumor size and apparent diffusion coefficient for differentiation of low- and high-grade clear-cell renal cell carcinoma. (February 2015) - Maruyama, Mitsunari; Yoshizako, Takeshi; Uchida, Koji; Araki, Hisayoshi; Tamaki, Yukihisa; Ishikawa, Noriyuki; Shiina, Hiroaki; Kitagaki, Hajime
Background: There is a significant correlation between tumor size and tumor grade for clear-cell renal cell carcinoma (RCC) in pathology. Thus, apparent diffusion coefficient (ADC) of clear-cell RCC might be influenced by tumor size. Purpose: To compare the utility of tumor size and ADC for distinguishing low-grade from high-grade clear-cell RCC. Material and Methods: Forty-nine patients undergoing preoperative magnetic resonance imaging were retrospectively assessed. ADC values were calculated using b-value combinations of 0 and 800 s/mm 2 at 1.5 T. Two radiologists in consensus measured ADC values via small region of interest (ROI) (mean ROI area, 88.8 mm 2 ; range, 80–108 mm 2 ) placement on an area of solid tumor on a single slice. Maximum tumor diameter was measured at the maximum tumor area. A single pathologist reviewed all pathological slides to determine the nuclear grade according to the Fuhrman classification. The utility of ADC, tumor size, and ADC/size ratio for distinguishing low-grade from high-grade tumors was assessed. Receiver-operating characteristic (ROC) analysis and regression analysis of the each index were performed. The correlation between ADC and tumor size was also investigated. Results: The 49 clear-cell RCC included 34 low-grade and 15 high-grade tumors. The differences of ADC, tumor size, and ADC/size ratio between high-grade and low-grade tumors were statistically significant ( P <0.05). The area under the ROC curve of ADC, tumor size, and ADC/size ratio were 0.802, 0.763, and 0.804 respectively. However, using regression analysis, only ADC ( P <0.05) was statistically significant index as independent risk factors for high-grade clear-cell RCC. Moreover, weak significant correlation was observed between tumor size and ADC (R 2  = 0.3865, P <0.01). Conclusion: There was a weak significant correlation between tumor size and ADC value of clear-cell RCC. Using ROC and regression analysis, ADC was statistically significant index for distinguishing low-grade from high-grade clear-cell RCC more than tumor size and ADC/size ratio.